Case Study: Indoor Air Quality and Respiratory Symptoms in Early Childhood in A Densely Populated Neighborhood of Region X - Meilinda, Vivi (Indonesian Health Journal, 2025)
Indoor air quality is a critical determinant of respiratory health in early childhood, particularly in densely populated areas with poor ventilation. This case study aims to identify the relationship between household air pollution exposure and respiratory symptoms among children in Region X. Ten households were purposively selected, and direct measurements of PM2.5, carbon monoxide, and humidity were conducted alongside behavioral observation and symptom recording over a two-week period. Results indicated that indoor PM2.5 and CO levels exceeded safety thresholds, with higher frequencies of symptoms such as coughing, wheezing, and shortness of breath among children living in poorly ventilated homes. These findings suggest that unhealthy, high-density housing conditions have a direct impact on child respiratory health. The study recommends community-based interventions focusing on ventilation improvement, reduction of indoor pollution sources, and health education. The findings provide an empirical basis for the development of healthy housing programs in densely populated urban settings.